PENGARUH MODEL DISCOVERY LEARNING BERBANTUAN WORDWALL TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN KELAS III SEKOLAH DASAR - Sari, Refiana; Nurwahidin, Muhammad; Hariyanto; Sowiyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem in this study is the low learning outcomes of Pancasila and Citizenship Education in grade III of SD Negeri 4 Metro Barat. This study aims to determine the effect of the application of the wordwall-assisted discovery learning model on the learning outcomes of Pancasila and Citizenship Education in grade III of SD Negeri 4 Metro Barat. The method used in this study is a quasi-experimental design with a non-equivalent control group design. This study uses a saturated sample technique with a sample size of 15 students and a population of 31 students. Data collection techniques use test techniques in the form of multiple-choice questions and non-test techniques in the form of observation sheets. Hypothesis testing uses a simple linear regression formula. The results of the study indicate that there is an effect of the application of the Wordwall-assisted Discovery Learning model on the learning outcomes of Pancasila and Citizenship Education in grade III of SD Negeri 4 Metro Barat.